Neuroanatomical phenotypes in a mouse model of the 22q11.2 microdeletion - Ellegood, J; Markx, S; Lerch, J P; Steadman, P E; Genç, C; Provenzano, F; Kushner, S A; Henkelman, R M; Karayiorgou, M; Gogos, J A (Molecular psychiatry, 2014)
Recurrent deletions at the 22q11.2 locus have been established as a strong genetic risk factor for the development of schizophrenia and cognitive dysfunction. Individuals with 22q11.2 deletions have a range of well-defined volumetric abnormalities in a number of critical brain structures. A mouse model of the 22q11.2 deletion ( Df(16)A +/− ) has previously been utilized to characterize disease-associated abnormalities on synaptic, cellular, neurocircuitry, and behavioral levels. We performed a high-resolution MRI analysis of mutant mice compared with wild-type littermates. Our analysis revealed a striking similarity in the specific volumetric changes of Df(16)A +/− mice compared with human 22q11.2 deletion carriers, including in cortico-cerebellar, cortico-striatal and cortico-limbic circuits. In addition, higher resolution magnetic resonance imaging compared with neuroimaging in human subjects allowed the detection of previously unknown subtle local differences. The cerebellar findings in Df(16)A +/− mice are particularly instructive as they are localized to specific areas within both the deep cerebellar nuclei and the cerebellar cortex. Our study indicates that the Df(16)A +/− mouse model recapitulates most of the hallmark neuroanatomical changes observed in 22q11.2 deletion carriers. Our findings will help guide the design and interpretation of additional complementary studies and thereby advance our understanding of the abnormal brain development underlying the emergence of 22q11.2 deletion-associated psychiatric and cognitive symptoms.